In vivo acute toxicity, laxative and antiulcer effect of the extract of Dryopteris Ramose - Nazir, Sana; Khan, Haroon; Khan, Sajjad Ali; Alam, Waqas; Ghaffar, Rukhsana; Khan, Sayed Hurmat Ali; Daglia, Maria (Cellular and Molecular Biology, 2021)
Dryopteris ramosa (D. ramosa) is one of the most traded medicinally important plants of Himalayan region. Apart from other uses, D. ramosa is traditionally also used to treat gastric ulcers and as a laxative. The present study was designed to investigate the role of methanolic crude extract of Dryopteris Ramosa (MEDR) in acute toxicity, against loperamide induced constipated mice model, antiulcer effect of methanolic extract of D. Ramosa and cholinomimetic like effect of methanolic extract of D. Ramosa. The crude extract was investigated for the presence of active compounds (secondary metabolites) such as alkaloids, flavonoids, carbohydrates, glycosides, terpenoids, phenolic compounds, saponins, and tannins following the standard methods. The antiulcer effect was investigated in mice using the ethanol induced ulcer model at various doses i.e. 50 mg/kg, 100 mg/kg and 200 mg/kg doses. Constipation was induced in the mice via loperamide (3mg/kg body weight). The control group received normal saline. Different doses of plant extracts (50, 100, 150 and 200 mg/kg body weight/day) were administered for 7 days. Various parameters like feeding characteristics, gastrointestinal transit ratio, body weight, fecal properties and the possible mechanism of action of D. Ramosa on intestinal motility were monitored. Various Phytochemicals like saponins, glycosides, flavonoids, tannins, phenols, carbohydrate, alkaloids and triterpenes were found in D. Ramosa. The acute toxicity study showed that MEDR was associated with no mortality except mild and moderate sedation at the highest tested doses (1500 and 2000 mg/kg). MEDR also showed significant antiulcer activity against ethanol-induced ulcerogenesis. The extract enhanced the intestinal motility, normalized the body weight of constipated mice and increased the fecal volume which are indications of laxative property of the herb. The 200 mg/kg body weight dose of the extract was found effective. The presence of various Phytochemicals such as flavonoids, glycosides and tannins might be responsible for the antiulcer activity of D. Ramosa. This study provides the scientific background for the folkloric use of D. Ramosa as antiulcer agent. The laxative action of the extract compares positively with Duphalac, (standard laxative drug). These findings have therefore evidence scientific background to the folkloric use of the herb as a laxative agent.